If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x(x + 8) = 4x + 32 Reorder the terms: 9x(8 + x) = 4x + 32 (8 * 9x + x * 9x) = 4x + 32 (72x + 9x2) = 4x + 32 Reorder the terms: 72x + 9x2 = 32 + 4x Solving 72x + 9x2 = 32 + 4x Solving for variable 'x'. Reorder the terms: -32 + 72x + -4x + 9x2 = 32 + 4x + -32 + -4x Combine like terms: 72x + -4x = 68x -32 + 68x + 9x2 = 32 + 4x + -32 + -4x Reorder the terms: -32 + 68x + 9x2 = 32 + -32 + 4x + -4x Combine like terms: 32 + -32 = 0 -32 + 68x + 9x2 = 0 + 4x + -4x -32 + 68x + 9x2 = 4x + -4x Combine like terms: 4x + -4x = 0 -32 + 68x + 9x2 = 0 Factor a trinomial. (-8 + -1x)(4 + -9x) = 0Subproblem 1
Set the factor '(-8 + -1x)' equal to zero and attempt to solve: Simplifying -8 + -1x = 0 Solving -8 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + -1x = 0 + 8 Combine like terms: -8 + 8 = 0 0 + -1x = 0 + 8 -1x = 0 + 8 Combine like terms: 0 + 8 = 8 -1x = 8 Divide each side by '-1'. x = -8 Simplifying x = -8Subproblem 2
Set the factor '(4 + -9x)' equal to zero and attempt to solve: Simplifying 4 + -9x = 0 Solving 4 + -9x = 0 Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -9x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -9x = 0 + -4 -9x = 0 + -4 Combine like terms: 0 + -4 = -4 -9x = -4 Divide each side by '-9'. x = 0.4444444444 Simplifying x = 0.4444444444Solution
x = {-8, 0.4444444444}
| -8-4x=3-7x | | -8.4x=58.8 | | 7a+3=14 | | 2lx+2l=18 | | 5(7-2m)+5=90 | | 2x^2-8x+15=11 | | 45-x=7 | | -7(2b+1)+(15b-3)=0 | | (-5u^3v^4+9u)+(-5u^3v^4-8u+8u^2v^2)+(-8u^4v^2+8u^3v^4)= | | 1.4q-1.3-1.8q=-1.4q-2.8 | | 4x+23=12x-73 | | 3x+4=59 | | 12-3=10x+3 | | y+34=18 | | 7+2x^2+4x^2=37 | | 5(5x+13)=25 | | 9m+3(m+12)-2= | | 0.45x+.05(2-x)=.10(-55) | | 4x(1-3x)=0 | | 5x+2=-5x+12 | | y=x^2-4x-1 | | 7z-8z=8z-6+4z | | 6w+13=3w-26 | | 3(2x+3)-5= | | -7(1)(-7)= | | 8x=18+5x | | 8x-2=40x+6 | | 3(5x+7)=-48+9 | | 48-x=7-4x | | 2a+6+9a+8= | | 10x-(3x-11)=25 | | x+4=59 |